وقائع سیرت سے استنباط احکام میں مباحث اصولیہ کا اطلاق: Application of the Principles of Islamic Jurisprudence in the deriving of injunctions from Sirah’ Incidents. (In the light of earlier and later Sirah writings - Dr. Hafiz Muhammd Naeem (Seerat Studies, 2023)
The biography of the Holy Prophet (PBUH) has always been an essential part of Islamic Literature. His earlier and later biographers did an Excellent Job as they recorded in detail every aspect of his life and produced a wonderful collection of classical writings. In this context, they practiced different approaches, styles and methodologies. Among these styles one is called Fiqh-al-Sirah in modern terminology, this methodology derives Juristic Implications and lessons from the Sirah incidents. This trend can found in Sirah books written by other great scholars like Ibn e Kathir (d.774 A.H.), Allama Maqrezi (d.845 A.H.), Imam Qastallani (d.923 A.H.), Imam Shami (d.942 A.H.), Imam Halabi (d.1044 A.H.) and Allama Zarqani (d.1122 A.H.) etc. These Implication and juristic rulings have been inferred from all the aspects of to Makki and Madni eras of Prophet`s life the lessons and instructions derived thus cover the religious, social, political, economic and other aspects of a Muslim’s life. These biographers have also applied the principles of Usool-e-Hadith and Usool-e- Fiqh in deriving the juristic implications from Sirah’ incidents. This article intends to explore this methodology adopted by biographers.